Penentuan Wali Nikah Bagi Anak di Luar Pernikahan Perspektif Hukum Islam dan Hukum Positif: The Determination of a Marriage Guardian for Children of Marriage from the Perspective of Islamic Law and Positive Law - Herlinda; Rofiq, Ainur; Kamilia, Nur (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The determination of a marriage guardian is one of the requirements for a valid marriage in Islamic law, especially for women. In the case of children born out of wedlock, problems arise because there is no blood relationship with the biological father, so he cannot be the guardian. This study aims to analyse the urgency of determining the marriage guardian in Islamic marriage law, as well as to examine the appointment of a marriage guardian for children born out of wedlock according to the perspective of Islamic law and Indonesian positive law. The method used is library research, analysing fiqh literature, the Compilation of Islamic Law (KHI), and the Constitutional Court Decision No. 46/PUU-VIII/2010. The results of the study show that the majority of scholars state that the biological father is not valid as a guardian, so the authority of the guardian is transferred to the judicial guardian. In practice, this is accommodated by Indonesian positive law through the authority of the Head of the Religious Affairs Office (KUA). Although legal solutions are available, social challenges such as stigma and discrimination against children born out of wedlock remain obstacles. This research contributes to strengthening the legal basis for the appointment of a judicial guardian and promotes an approach that considers justice, child rights protection, and the principles of maqāṣid al-Syarī‘ah in the reform of Islamic family law.